2006
DOI: 10.1093/cercor/bhl102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Layer-Specific Genes in Mammalian Neocortex

Abstract: We examined the expression patterns of 4 layer-specific genes in monkey and mouse cortices by fluorescence double in situ hybridization. Based on their coexpression profiles, we were able to distinguish several subpopulations of deep layer neurons. One group was characterized by the expression of ER81 and the lack of Nurr1 mRNAs and mainly localized to layer 5. In monkeys, this neuronal group was further subdivided by 5-HT2C receptor mRNA expression. The 5-HT2C(+)/ER81(+) neurons were located in layer 5B in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 62 publications
9
118
1
3
Order By: Relevance
“…Studies in our laboratory and those of other investigators have shown that these two genes are preferentially expressed in the subplate in rodents and nonhuman primates (Arimatsu et al 2003;Watakabe et al 2007;Hoerder-Suabedissen et al 2009). …”
Section: Nurr1 and Ctgf Expression In The Human Developing Cortexmentioning
confidence: 51%
“…Studies in our laboratory and those of other investigators have shown that these two genes are preferentially expressed in the subplate in rodents and nonhuman primates (Arimatsu et al 2003;Watakabe et al 2007;Hoerder-Suabedissen et al 2009). …”
Section: Nurr1 and Ctgf Expression In The Human Developing Cortexmentioning
confidence: 51%
“…Double and triple ISH experiments were performed following protocols described previously (Watakabe et al, 2007). An example of the procedure used to quantify double-labeled cells is shown in supplemental Figure S1 (available at www.jneurosci.org as supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Another comparative gene expression analysis in adult mouse and marmoset brain using microarray analysis did not report major differences (Datson et al, 2009). However, studies comparing gene expression in postnatal monkey and mouse brain identified multiple expression differences in gene expression within cortical layers and cell populations (Takahata et al, 2006(Takahata et al, , 2009Watakabe et al, 2006Watakabe et al, , 2007. Therefore, to find species-specific gene expression, it is important to analyze gene expression at the cellular level in specific regions for higher cognitive functions with high resolution in situ hybridization approaches.…”
Section: Comparative Analysis Of Mouse and Monkey Brainmentioning
confidence: 99%
“…The most commonly used "primate model species" for studying brain anatomy and behavior are Old World monkeys, typically rhesus monkeys (Macaca mulatta), and long-tailed (Macaca fascicularis) macaques because of resource availability and historical descriptions of these species (Rakic, 1988;Takahata et al, 2006Takahata et al, , 2009Watakabe et al, 2006Watakabe et al, , 2007. However, the disadvantages of using such monkeys for experimental manipulations include their large body size, inefficient fertility, and slow development to sexual maturity.…”
Section: Introductionmentioning
confidence: 99%